Modeling Enterprise Authorization: A Unified Metamodel and Initial Validation - Korman, Matus; Lagerström, Robert; Ekstedt, Mathias (Complex Systems Informatics and Modeling Quarterly, 2016)
Authorization and its enforcement, access control, have stood at the beginning of the art and science of information security, and remain being crucial pillar of security in the information technology (IT) and enterprises operations. Dozens of different models of access control have been proposed. Although Enterprise Architecture as the discipline strives to support the management of IT, support for modeling access policies in enterprises is often lacking, both in terms of supporting the variety of individual models of access control nowadays used, and in terms of providing a unified ontology capable of flexibly expressing access policies for all or the most of the models. This study summarizes a number of existing models of access control, proposes a unified metamodel mapped to ArchiMate, and illustrates its use on a selection of example scenarios and two business cases.